Police Policy in Combating Narcotics Crime (Study at Medan Police Headquarters) - Tampubolon, Siti Rohani; Isnaini; Suhaidi (JURNAL MERCATORIA, 2024)
This study aims to analyze the policies of the Indonesian National Police (Polri) in combating narcotics crimes (study at Polrestabes Medan). Medan City is one of the areas most affected by narcotics trafficking, both from local syndicates and international networks. Polri policies include law enforcement, prevention through education and socialization, and rehabilitation for narcotics users. Based on this, the focus of the problems in this study are First, how is the Polri policy in combating narcotics crimes (Study at Polrestabes Medan) Second, What are the obstacles faced by Polri in combating narcotics crimes (Study at Polrestabes Medan). This study uses normative-empirical juridical research with descriptive data analysis. The results of the study show that although Polri has carried out various significant law enforcement operations and prevention programs, challenges such as the involvement of certain officers, high demand for narcotics among the community, limited rehabilitation facilities, and the complexity of international narcotics networks are still major obstacles. Therefore, efforts are needed to improve internal supervision, increase international cooperation, and increase the capacity of community-based rehabilitation and prevention programs.